Helicopter MGB oil system failure analysis using influence diagrams and random failure probabilities. (April 2015) - Rashid, H.S.J.; Place, C.S.; Mba, D.; Lim, R.; Healey, A.; Kleine-Beek, W.; Romano, M.
Highlights: We examined causal factors leading to failure of helicopter MGB due to oil loss. The influence diagram concept is used to assess reliability of MGB oil system. This is critical as many helicopter accidents were caused by inflight MGB oil loss. We developed a model to estimate MGB oil system components failure probabilities. The model feeds into new MGB designs and maintenance programme regulations by EASA. Abstract: This paper discusses a research launched by the European Aviation Safety Agency (EASA) to enhance helicopter safety performance through advanced reliability assessment of Type A helicopter main gearbox (MGB) lubricating systems. Oil starvation within a helicopter MGB will lead to increased friction between components, and an escalation in component surface temperatures that can result in subsequent thermal expansion and failure of the gearbox components. This is a concern for the industry as increasing numbers of helicopter accidents are witnessed that have been caused due to such loss of lubrication. This paper reports on a new method for assessing reliability of pressurized MGB lubrication systems. Safety risk modeling which included fault tree analysis (FTA) of MGB oil system related accidents and incidents was conducted. This led to the identification of prevailing failure modes for MGB lubrication systems and key contributing components. Reliability of the MGB lubrication systems at component level was accordingly investigated using The influence diagram (ID) approach. Random failure probabilities of MGB components were integrally used within the ID to map the infinite possible combinations of failures causes and modes. The theory is applicable to other pressurized lubrication systems. Results are discussed.